2009
DOI: 10.12693/aphyspola.116.185
|View full text |Cite
|
Sign up to set email alerts
|

Transient Disturbance in a Half-Space under Generalized Magneto-Thermoelasticity with Internal Heat Source

Abstract: The transient waves caused by a line heat source with a uniform velocity inside isotropic homogeneous thermoelastic perfectly conducting half-space permeated into a uniform magnetic field are studied. The formulation is applied under three theories of generalized thermoelasticity: Lord-Shulman theory with one relaxation time, Green-Lindsay theory with two relaxation times, as well as the classical dynamical coupled theory. The problem is reduced to the solution of three differential equations by introducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
(22 reference statements)
0
25
0
2
Order By: Relevance
“…We have found that the time has a significant effect on the field quantities. Figures 7, 8, 9, 10, 11, and 12 show the variation of the temperature, displacement components, u, v, and stress components, σ x x , σ yy , σ xy , and induced magnetic field, h, with time t at 8,9,10,11,12,13, and 14, the solid lines refer to the case with reinforcement (WRE) and the dotted lines refer to the case without reinforcement (NRE), i.e., (α = 0, β = 0, and (μ L − μ T ) = 0). It is easy to see from Figs.…”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…We have found that the time has a significant effect on the field quantities. Figures 7, 8, 9, 10, 11, and 12 show the variation of the temperature, displacement components, u, v, and stress components, σ x x , σ yy , σ xy , and induced magnetic field, h, with time t at 8,9,10,11,12,13, and 14, the solid lines refer to the case with reinforcement (WRE) and the dotted lines refer to the case without reinforcement (NRE), i.e., (α = 0, β = 0, and (μ L − μ T ) = 0). It is easy to see from Figs.…”
Section: Numerical Examplementioning
confidence: 99%
“…Singh [6] studied a problem on wave propagation in an anisotropic generalized thermoelastic solid and obtained a cubic equation, which gives the dimensional velocities of various plane waves. Recently, a number of investigations [7][8][9][10][11][12] have been carried out using the aforesaid theories of generalized thermoelasticity under the effect of a magnetic field.…”
mentioning
confidence: 99%
“…This results are showing inOthman et al (2009). By comparing the figures of solutions obtained under the three thermoelastic theories, important phenomena are observed: Distribution…”
mentioning
confidence: 67%
“…Othman and Lotfy [27] studied two-dimensional problem of generalized magneto-thermoelasticity under the effect of temperature dependent properties. Othman and Lotfy [28] studied transient disturbance in a half-space under generalized magneto-thermoelasticity with moving internal heat source. Othman and Lotfy [29] studied the plane waves in generalized thermo-microstretch elastic half-space by using a general model of the equations of generalized thermo-microstretch for a homogeneous isotropic elastic half space.…”
Section: Introductionmentioning
confidence: 99%